Impact test and bioactivity properties of polycaprolactone (PCL) by addition of nano-montmorillonite (MMT) and hydroxyapatite (HA) - Abdul Haq, Reazul Haq; Wahab, Mohd Saidin; Wahit, Mat Uzir (Trans Tech Publications, 2019)
This report described the Impact Test result and Bioactivity Properties of biodegradable Polycaprolactone (PCL) blend with nano- Montmorillonite (MMT) and Hydroxyapatite (HA). The amount of nano-MMT is varies from 2 to 4 by weight % meanwhile the amount of HA is fixed to 10 by weight percentage (wt%). The addition of nano-MMT and HA filler is to tune and indirectly improve the mechanical and bioactive properties of PCL. The samples for these test are injected from injection molding machine. The Impact test are conducted using Charpy Method. From the analysis it is found that the toughness of PCL are decreased by the addition of these fillers. PCL/MMT composites gives a better result compare to PCL/MMT/HA composites. This is due to the HA characteristic which is brilttle and tends to reduce the ductile properties of the polymer. From the Simulated Body Fluis (SBF) result, formation of apatite layer at the surface of the composites is evidence of excellent bioactivity properties of HA. The enhance of bioactivity has been proved while incorporation of HA into PCL/MMT composite. SEM-EDX image showed the bulk formation of apatite layers on the composite surface with 10 wt% HA after 3 days immersed in SBF solution.